The Defense Mechanisms and The Behaviour of The Criminal Mind - Oruç, Derya (Akademisyen Yayınevi Kitap DOI Portalı, 2023)
This book examines the relationship between defense mechanisms and the behaviors of a criminal mindset. The author explores the reasons behind a criminal mindset and how criminals utilize defense mechanisms, while also considering the impact of the superego and object relations on personality disorders. The book also delves into narcissistic personality disorder and extensively discusses the defense mechanisms of individuals with this disorder. The representations of narcissistic characters in literary texts are also examined, with examples such as Robert Browning’s T̈he Last Duchess,Ẅilliam Shakespeare’s Öthello,änd Oscar Wilde’s T̈he Picture of Dorian Grayb̈eing analyzed. This book is adapted from the thesis titled D̈efense Mechanisms and the Behaviors of a Criminal Mindset,ẅritten under the supervision of Prof. Dr. Mehmet Oğuz Cebeci from Yeditepe University’s Institute of Social Sciences.